An Analysis on the Effect of Television Show on the Students’ Character of Elementary School Students in Bangkinang Kota - Mufarizuddin, Mufarizuddin; Fauziddin, Mohammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
It is found that some elementary school students favor to talk and behave one of the cinema, namely